Global-local visual processing impacts risk taking behaviors, but only at first - Lim, Stephen Wee Hun; Yuen, Alexander Y. L.; Tong, Eddie M. W. (Frontiers in Psychology, 2015)
We investigated the impact of early visual processing on decision-making during unpredictable, risky situations. Participants undertook Navon’s (1977) task and attended to either global letters or local letters only, following which they completed the Balloon Analogue Risk Task (BART). It was observed that global-focused individuals made more balloon pumps during the BART (i.e., took more risk), whereas local-focused individuals took less risk, albeit only initially. The theory of predictive and reactive control systems (PARCS) provides an excellent account of the data. Implications and future directions are discussed.